Challenges of Information Technology and Cultural Integration in Education in Timor-Leste - Moruk, Selviana; Noronha, Alise de Fatima (The Indonesian Institute of Science and Technology Research, 2025)
The integration of information technology in education presents significant opportunities to improve access, equity, and quality in learning. However, in developing countries like Timor-Leste, the process faces complex challenges that are both infrastructural and cultural. This study aims to explore the key barriers to implementing educational technology in Timor-Leste through a structured literature review. Using a qualitative descriptive approach, 15 core publications were selected from a total of 225 sources retrieved from the Dimensions database. Thematic analysis identified five central issues: limited technological infrastructure, inadequate teacher readiness, restricted access to digital resources, cultural resistance, and weak institutional collaboration. Findings reveal that rural and border regions suffer from minimal internet connectivity, lack of digital devices, and low digital literacy among educators. Moreover, cultural factors—such as the perception of technology as an external influence and the undervaluing of local wisdom—create resistance to educational innovation. The study highlights the importance of integrating local cultural values into digital curricula, implementing targeted ICT training for teachers, and promoting inclusive, multicultural education. Policy implications suggest that long-term investment in infrastructure, community-based strategies, and formalized partnerships between institutions are essential to ensure successful digital transformation in education. The findings provide a framework for designing culturally responsive and sustainable education policies in Timor-Leste and similar contexts.